An Apple a Day? Adult Food Stamp Eligibility and Health Care Utilization Among Immigrants - Chloe N. East; Andrew I. Friedson (Institute of Labor Economics (IZA), 2018)
In this study, we document the effect of Food Stamp access on adult health care utilization. While Food Stamps is one of the largest safety net programs in the U.S. today, the universal nature of the program across geographic areas and over time limits the potential for quasi-experimental analysis. To circumvent this, we use variation in documented immigrants' eligibility for Food Stamps across states and over time due to welfare reform in 1996. Our estimates indicate that access to Food Stamps reduced the likelihood of an adult visiting a physician more than twice in one year, but had no significant effect on the likelihood of having any physician visits. This result does not appear to be due to changes in physical or mental health, or due to individuals with common chronic health conditions, leaving open the possibility that changes in nutrition or resources may reduce the need for physician visits. Additionally, we find that for single women, Food Stamps increased the affordability of specialty health care, which may have further reduced the need for physician visits. These findings have important implications for cost-benefit analyses of the Food Stamp program, as reductions in health care utilization due to Food Stamps may offset some of the program's impact on the overall government budget due to the existence of government-provided health insurance programs such as Medicaid.
Keywords: H51; H53; H75; I11; I18; Q18; 330; Food Stamps; immigrants; health care